Clay components mineralogy and smears slides analysis for the cores of DOMES Site C, Pacific Ocean - James R Hein; Christina Gutmacher; Jacquelyn Miller (PANGAEA, 1976)
DOMES area C sediment is quite heterogeneous, but most commonly is classified as mud (clay minerals, quartz, and feldspar) or siliceous ooze. However, in several samples Fe-Mn micronodules, globules and aggreqates are the major sediment components. Calcareous nannofossil ooze characterized only one sample, core 18A-1-8 and calcite (reworked limestone?) is present in several other cores, but never as a major compoment. Volcanic ash (glassy mud) is the major sediment type in several cores.
Supplement to: Hein, JR et al. (1976): DOMES Area C, General statement about mineralogy, diagenesis and sediment classification. in: Deep Ocean Mining Environmental Study, N.E. Pacific Nodule Province, Site C, Geology and Geochemistry, U.S. Geological Survey Open File Report. U.S. Geological Survey, 63-80, https://store.pangaea.de/Projects/NOAA-MMS/DOMES_Hein_1976.pdf